Psoas abscess secondary to atypical appendicitis in pregnancy. A case report - Viviana de la Caridad Sáez Cantero; Mario Joel Arroyo Díaz; Leonel Hernández Torres; María Teresa Medel Agüero (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2023)
The psoas abscess is a rare infectious disease that is difficult to diagnose, characterized by a purulent collection at the level of this muscle, which causes a systemic inflammatory response syndrome. The infection can be primary by hematogenous dissemination, or secondary, from a nearby infectious focus. Its presentation during pregnancy is rare, and the primary form predominates, which is why it was decided to write this article. The case of a pregnant woman with a gestational age of 28.4 weeks who was admitted due to inguinal pain with subsequent irradiation to the right hip, flank, and lumbar region; flexed posture of the right hip and analgesic gait, as well as the appearance, nine days after the onset of symptoms, of a painful mass between the right iliac fossa and flank it is presented. The findings of the abdominal ultrasound and MRI allowed the diagnosis of an appendiceal plastron with a retrocecal appendix, as well as a right psoas abscess, which were treated with antibiotic therapy and percutaneous drainage of the abscess, with satisfactory results. Secondary psoas abscess may constitute the debut of atypical retrocecal appendicitis, and its diagnosis requires a high level of suspicion due to its non-specific symptoms.